Cirrhosis in Transition: Emerging Concern in a Post-Pandemic World - Turan Gökçe, Dilara; Akdoğan, Meral (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Turan Gökçe D, Akdoğan M. Cirrhosis in transition: emerging concern in a post-pandemic world. Turk J Gastroenterol. 2025;36(1):1-2.